Tasawuf Transnasional: Integrasi Spiritualitas Sufi Senegal Kontemporer dan Tradisi Tasawuf Indonesia - Muhammad Rif’an (PT. Hasba Edukasi Mandiri, 2026)
Sufism, as the spiritual dimension of Islam, has undergone cross-regional and transnational development. This article examines the integration of contemporary Senegalese Sufi spirituality with Indonesian Sufi traditions within the context of global Islam. Senegalese Sufism, which has developed through major Sufi orders such as the Murīdiyyah and Tijāniyyah, demonstrates a form of Sufism that is not only spiritual but also social and cultural in nature. Meanwhile, Indonesian Sufism has evolved within the framework of Islamic moderation rooted in pesantren traditions and Sufi orders. This study employs a qualitative approach using library research methods and comparative analysis of relevant scholarly literature. The findings indicate that the integration of Senegalese and Indonesian Sufism is grounded in shared core Sufi values, including dhikr, obedience to the murshid, social ethics, and adaptation to modernity. These findings affirm that Sufism functions as a spiritual bridge within transnational Islam, reinforcing a moderate and inclusive expression of Islam.